Pemeriksaan Gula Darah dan konseling Kesehatan Sebagai Upaya Deteksi Dini Penyakit Diabetes Melitus di Car Free Day (CFD) Purwodadi Kabupaten Grobogan - Wahyu Riniasih; Festy Mahanani; Suryani; Wahyu Dewi Hapsari; Wahidah Nur Khasanah; Abdul Rasyid Ariadi; Novita Rina Rahmasari (LPPM AN Nuur, 2024)
Background : Diabetes is often associated with genetic factors, as well as unhealthy lifestyle and eating habits, which result in complications affecting other organs and leading to additional diseases. The increasing number of diabetes mellitus (DM) patients each year demonstrates that there is still a lack of educational and preventive efforts carried out by healthcare professionals and health academics towards the community. purpose of this community service is to provide blood sugar testing services to the public attending Car Free Day (CFD) every Sunday on Jl. R. Suprapto Purwodadi, Grobogan Regency. This service also includes educational counseling related to DM. Methodology : used involves health counseling regarding DM, health assessments, and blood sugar level checks. There are three main steps during the activity: respondent selection, blood sugar measurement, and DM counseling. Results : of this service show an increase in understanding and awareness about the importance of early prevention after DM counseling was provided. Conclusion : it is necessary to provide health counseling to all individuals at high risk for DM and to regularly conduct blood sugar screenings for all residents of Grobogan Regency.